Analisis Prakonsepsi terhadap Kemunculan Miskonsepsi pada Materi Statistika - Aisyah Aisyah; Andika Setyo Budi Lestari; Miftahul Khoiri (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2026)
Many students still face difficulties in understanding statistics because inaccurate preconceptions often develop into misconceptions. This condition is important to study since misconceptions can hinder the mathematics learning process and reduce the quality of students’ conceptual understanding. This study aims to analyze in depth how preconceptions affect the emergence of misconceptions among senior high school students in learning statistics. The research employed a qualitative descriptive method with a case study approach, involving three tenth-grade students from State Senior High School 1 Purwosari who were selected through purposive sampling based on high, medium, and low achievement categories. Data were collected through diagnostic tests in the form of essay questions to reveal students’ preconceptions and in-depth interviews to explore their reasoning, then analyzed descriptively. The findings show that students with accurate preconceptions did not experience misconceptions, students with partially correct preconceptions developed classificational, theoretical, and correlational misconceptions, while students with incorrect preconceptions experienced more complex misconceptions, such as considering the median as the largest value and failing to relate changes in data to the properties of the mean, median, and mode. The study concludes that inaccurate preconceptions directly contribute to the emergence of various forms of misconceptions. The implication is that teachers need to detect, identify, and correct students’ preconceptions from the beginning of the learning process so that misconceptions can be minimized and students’ understanding of statistics can develop more comprehensively.